Mangroves on the Edge: Anthrome-Dependent Fragmentation Influences Ecological Condition (Turbo, Colombia, Southern Caribbean) (2015)
ABSTRACT: Marine protected areas are commonly seen as the most effective strategy for protecting mangroves from external human pressures but little is known about the role of public land-tenure contexts (dense settlements, agricultural or range lands and wild anthromes) on clearing rates, patch properties, and ecological condition. We addressed the following questions using a peri-urban to wild gradient along the anthropogenic coastal-scape in Turbo Municipality (Colombia, Southern Caribbean): Do the different deforestation rates observed under peri-urban, rural, military-protected and wild land-use-and-tenure contexts, promote distinctive fragmentation patterns? Do these patterns influence loggers’ access and ultimately ecosystem ecological condition? Loss rate (1938–2009) was the greatest in peri-urban mangroves and positively correlated with urban edge and patch density. Pasture edge was highest in rural mangroves while mean patch area was higher in protected and wild mangroves. An Anthropogenic Disturbance Index (ADI) was strongly correlated with reduced mean patch area and increased patch density, due to increased trampling and logging, that ultimately promoted high densities of thin (diameter: <5 cm) Laguncularia racemosa trees but had no significant effect on the presence of a dominant benthic gastropod. In conclusion, both protection and remoteness were effective in reducing anthropogenic edges and fragmentation, and thus contributed to a high ecological condition in mangroves at a major deforestation hotspot.